Syntheses, Structures and Optoelectronic Properties of Spiroconjugated Cyclic Ketones1. Issue 14 (24th April 2016) - Wilbuer, Jennifer; Schnakenburg, Gregor; Esser, Birgit
Abstract: Synthetic investigations towards spiroconjugated ketones and derivatives thereof are presented. These studies led to the development of a short procedure for the synthesis of spiroconjugated tetraketone1 in two steps with 10 % overall yield and the first‐time synthesis of spirocyclic trindone2 . The optoelectronic properties of these compounds based on spectroscopic and electrochemical measurements in combination with DFT calculations as well as their molecular structures in the solid state are presented and discussed. Abstract : A two‐step synthesis to a spiroconjugated tetraketone has been developed, which proceeds via a novel spirocyclic trindone. Optoelectronic investigations revealed the effect of spiroconjugation in the trindone, and intramolecular C–H··· O hydrogen bonding was observed in solution and in the solid state.